Surviving and Overcoming Poverty: Experiences of Quondam Poor Individuals in a Philippine City - Jacinto, John Wayne V. (Silliman Journal, 2024)
This paper explored the processes undertaken by quondam poor individuals to survive and overcome poverty in Dapitan City, Philippines. Dapitan City is one of the third-class cities and, unlike other cities in the Philippines, is not highly urbanized. Hence, surviving and overcoming poverty in this economic condition yields a different reality. This pilot study employed the grounded theory approach, which generated a paradigm based on the experiences of quondam poor individuals. Central to the participants’ experiences in surviving and overcoming poverty were the realization and acceptance of their conditions and their determination to succeed and achieve their goals. The choice and use of means of overcoming poverty were relative to the participants’ contexts and personal-social conditions. Surviving and overcoming poverty is a conglomeration of internal and external factors in the lives of individuals.